A categorização e a recategorização de objeto de discurso como estratégia de construção de face : uma análise de depoimentos de Orkut - Gonçalves, Lorena Santana (2012)
Orkut testimonial is a type of text genre in which the interaction between the users of this social networking website is made from a common factor: the owner of the profile. This owner is taken as the object of his/her friend’s discourse and he/she is (re)categorized so that the effect of this text construction embodies the face claim of both the owner of the profile and his/her friend who has written the testimony. Based on this assumption, this paper focuses on the relationship between the (re)categorization of the object of the discourse and the social image building in Orkut testimonials, in which the categorization is considered an important language feature that contributes to the representation of the social image. To understand the issues related to public image, this study presents an overview of some literature regarding Pragmatic theories which deal with this theme considering the face claim and linguistic politeness. Some authors, such as Goffman (1980, 1992), Lakoff (1973, 1975), Leech (1983) and Brown & Levinson (1975), are of paramount importance for the goals of this research, since they built their theories upon a traditional point of view, emphasizing the speaker’s intention who always aims to save his/her own face using acts of politeness. It is also highlighted some authors who has provided the field of Textual Linguistic research with remarkable insights into the concepts of referral and the construction of the discourse object: Mondada & Dubois (2003), Koch (2004, 2005b, 2008a, 2008b), Marcuschi (2007, 2008) and Cavalcante (2011). From the interface of these two fields of study, it is presented an analysis of the social image construction in the genre of Orkut testimonials, which is divided under three main headings: Praise, rememorizes and Thanks.